The impact of EU integration on the Portuguese distribution of employees’ earnings - Andrade, João A. S. (2010)
The accession of Portugal to the EU resulted in several important and different shocks to the Portuguese economy, imposing among others a real positive and lasting effect on employees’ earnings. This paper analyses the impact of Portugal’s accession to the EU in terms of employees’ earnings inequality using data for the years 1985 and 1991 at the Concelhos level from the Quadros de Pessoal database. The two earnings distributions are compared using cardinal measures of inequality and the Lorenz stochastic dominance approach (Araar Abelkrim and Jean-Ives Duclos). The Relative Distribution approach (Mark S. Handcock and Martina Morris) is applied in order to inspect the overall differences of the two distributions and split the overall relative distribution into location and shape shift effects. The technique of covariate decomposition is used to assess the importance of the human capital/education distribution for the explanation of the evolution of the employees’ earnings distribution from 1985 to 1991. This paper contributes to the literature on inequality by focusing on country specific data at the regional and sectoral level and by applying distinct empirical methodologies that clarify the nature of inequality at the aggregate level. During the period under analysis employees’ median and average earnings registered a strong growth pointing to a sort of honeymoon effect of EU integration on Portuguese employees’ earnings. The paper also contributes to the literature by sorting out this kind of honeymoon effect and emphasizing it as a case to be analyzed in other countries since, in the absence of appropriate country policies, it can jeopardize future growth.